#TITLE_ALTERNATIVE# - MUBARAQ (Pembimbing : Sonny Winardhie, Ph.D.), MUNAJAT
One of inversion method that we have known is simultaneous inversion. Simultaneous inversion uses partial stack data with variations of angle (near, middle and far offset stack). The partial stack data will be inverted simultaneously using wavelets which were estimated from every stack. The results from simultaneous inversion are acoustic impedance (AI), shear impedance (SI) and density (ρ). The AI, SI and ρ are calculated to become reservoir petrophysics parameters such as Lambda-Rho, Mu-Rho and Lambda-over-Mu which are sensitive to lithology differences and fluid identifications. The results from simultaneous inversion and other calculated parameters were used to delineate sandstones. In this study, resulted that lambda over mu (λ/μ) parameter is the best parameter for discriminating the potential sandstones. From the analysis result, obtained that low Lambda over Mu (λ/μ) value related potential sandstone. Mu-rho parameter can distinguish where is the calcareous sandstone, sandstone and shale. Result analysis show the high value of mu-rho are appearance sandstoneÃ‚Â’s indicator. To understand lithology laterally, uses mapping and analysis both of parameters which obtained from slicing on horizon target.